how about we multiply the entire equation
1/p+1/(p-45) = 1/30
by
30p(p-45)
30(p-45) +30p = p(p-45)
30 p - 1350 + 30 p = p^2 -45 p
p^2 -(45+30+30)p + 1350 = 0
p^2 - 105 p + 1350 = 0
I need help understanding how to cross-multiply addition of inverse functions. I'm given this,
1/p+1/(p-45) = 1/30
The answer goes to p^2-105p+1,350 = 0.
My method has been adjusting the ratios of the numerator and denominators to give,
[30(p-45)]/[30p(p-45)]+[30p]/[30p(p-45)] = [p(p-45)]/[30p(p-45)]
I add the like denominators on the left, and then cross multiply in order to cancel the [30p(p-45)] term.
1 = p(p-45)/1,350 ==> p^2-45p+1,350 = 0
How is my professor getting -105p instead of -45p?
Thanks
1 answer